ANKAI SITELU: KOREOGRAFI TERINSPIRASI DARI SISTEM KEKERABATAN PADA MASYARAKAT KARO - DAMANIK, DESY WULAN PITA SARI (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Ankai sitelu is taken from the Batak Karo language, the word ankai means understanding and sitelu which means sitiga. If these three words are interpreted, they mean a dance that originates from understanding rakut sitelu. " ankai sitelu" is a dance work inspired by the Batak Karo kinship system, namely rakut sitelu. Rakut sitelu consists of sukut, kalimbubu, and anak beru. Sukut is the party who is the host in a traditional or ritual ceremony, kalimbubu is the party who is highly respected because he is considered to be the representative of dibata (god) on earth who gives tendi and blood, while anak beru is the party who does the sukut work in traditional ceremonies and rituals. This work takes the essence of balance in the rakut sitelu system with traditional karo dance movement patterns which are developed according to broader teba movement intensity, volume, level and time. Ankai Sitelu's work is a group choreography consisting of three female dancers, a total of three dancers who will be composed in a large group and small group composition by paying attention to the composition of the parts. The number of three dancers is analogous to three social positions in the Rakut Sitelu kinship system. This work uses the exploration method as an initial part in developing the creativity of the creation process, improvisation to find movements by chance or spontaneously, composition to arrange the movements that have been obtained, as well as periodic corrective evaluation of the process. This work is expected to provide information about the meaning and values contained in Rakut Sitelu. Keywords: Rakut sitelu, balance, Karo Batak tradition